Proceedings of the Ocean Drilling Program, 143 Scientific Results 1995
DOI: 10.2973/odp.proc.sr.143.252.1995
|View full text |Cite
|
Sign up to set email alerts
|

Early Cretaceous Shallow-Water Benthic Foraminifers and Fecal Pellets from Leg 143 Compared with Coeval Faunas from the Pacific Basin, Central America, and the Tethys

Abstract: Early Cretaceous shallow-water benthic foraminifers and fecal pellets were recovered from Allison and Resolution guyots in the western Mid-Pacific Mountains (MPM) during Ocean Drilling Program Leg 143. These faunas are used to date the carbonate platform owing to the near absence of other microfossils. Four sites contained the Early Cretaceous assemblages: Site 865 on Allison Guyot, and Sites 866, 867, and 868, which were drilled as part of a transect across the perimeter of Resolution Guyot.Of these sites, Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 12 publications
1
26
0
1
Order By: Relevance
“…Novalesia angulosa (Figure 5d, e) was described from the Albian of the Spanish Pyrenees as Spiroplectamminoides by Magniez 1972, and later assigned to Novalesia (Magniez, 1974). The known range is late Aptian to Albian (Arnaud-Vanneau and Sliter, 1995). This species is common in the El Madroño samples.…”
Section: Foraminiferal Assemblage and Agementioning
confidence: 99%
“…Novalesia angulosa (Figure 5d, e) was described from the Albian of the Spanish Pyrenees as Spiroplectamminoides by Magniez 1972, and later assigned to Novalesia (Magniez, 1974). The known range is late Aptian to Albian (Arnaud-Vanneau and Sliter, 1995). This species is common in the El Madroño samples.…”
Section: Foraminiferal Assemblage and Agementioning
confidence: 99%
“…7E, F). The MidPacific Mountains, dated to 123 -132 Ma [Arnaud-Vanneau & Sliter, 1995;Jenkyns, 1995;Jenkyns et al, 1995;Pringle & Duncan 1995], are broadly observed southwest of the Hawaiian Ridge (Fig. 1, 5).…”
Section: Isolating Swell Bathymetrymentioning
confidence: 99%
“…Known range: Upper Berriasian (Canérot, 1984;Bucur, 1988) -Aptian (Laug et al, 1980;Voznesenskii et al, 2002 (Brönnimann & Conrad, 1967); Middle-Upper Berriasian of Ain, Savoie, France (Darsac, 1983); Barremian of Neuchatel area, Switzerland (Arnaud-Vanneau and Masse, 1989); Probable Hauterivian of the Mid-Pacific Mts. (Arnaud-Vanneau and Sliter, 1995). Known range: Berriasian (Darsac, 1983) -Lowermost Aptian (Brönnimann and Conrad, 1967 Darsac (1983;Pl.…”
Section: Systematic Partmentioning
confidence: 99%